A new species of Malus in China, Malus shizongensis Liu sp. nov - Zhen-zhong LIU; Zhong-xing LI; Hua GAO; Cha-na BAO (Journal of Integrative Agriculture, 2020)
Based on morphological, molecular biological, and molecular systematic studies, we describe here a new species of Malus from Yunnan, China. We compared the morphology of this new species, Malus shizongensis Liu sp. nov, with three Malus species, including M. hupehensis, M. baccata, and M. micromalus. Although the appearance of M. shizongensis was similar to these three species, it differed in height, branch color, branch hair, and flower color. To better identify the taxonomy of this new species, genome of M. shizongensis and that of seven Malus species, including M. prunifolia, M. sylvestris, M. sieversii, M. hupehensis, M. baccata, M. robusta, and M. micromalus were analyzed. A phylogenetic tree based on genome analysis indicated that M. shizongensis was close to M. hupehensis. Furthermore, M. shizongensis had its species-specific SNPs, and the number of species-specific SNPs was similar to that of three close species (M. hupehensis, M. baccata, and M. micromalus). Based on the above information, we named this new species as M. shizongensis Liu sp. nov.